Understanding sport a socio-cultural analysis - Horne, John, 1955-; Horne, John, 1955-; T&F eBooks (Milton Park, Abingdon, Oxon ; New York : Routledge, 2013)
"In the decade or more since publication of the first edition of Understanding Sport, both sport and wider global society have undergone profound change. In this fully updated, revised and expanded edition of their classic textbook, John Horne, Alan Tomlinson, Garry Whannel and Kath Woodward offer a critical and reflective introduction to the relationship between sport and contemporary society and explain how sport remains an important agent and symptom of socio-cultural change. Fully integrating historical, sociological, political and cultural analysis, the book covers every key topic in the study of sport and society, including: - debate, interpretation and theory - sport and the media - sport and the body - sport and politics - commercialization - globalization. Retaining the accessibility and scholarly rigour for which Understanding Sport has always been renowned, this new edition includes entirely new chapters on global transformations, sports mega-events and sites, sporting bodies and governance, as well as a succinct guide to researching sport. With review and seminar questions included in every chapter, plus concise, helpful guides to further reading, Understanding Sport remains an essential textbook for all courses on sport and society, the sociology of sport, sport and social theory, or social issues in sport"--
1. Industrial society, social change and sports culture -- 2. Case studies in the growth of modern sports -- 3. Debates, interpretations, theories -- 4. Social stratification and social division in sport -- 5. The social construction of identity and cultural reproduction -- 6. Sport and representation -- 7. Sporting bodies : disciplining and defining normality -- 8. Sport, the state and politics -- 9. Governance and sport -- 10. The labour market -- 11. Sport, commercialisation and commodification -- 12. Global transformations -- 13. Sport spaces, sites and events -- 14. Conclusion : methods for understanding sport culture.
Prev. ed. cataloged under Horne, John.
Includes bibliographical references (p. 236-264) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Sports -- Great Britain -- Sociological aspects; Sports -- Great Britain -- History; Electronic books